IN THE UZBEK LANGUAGE, THE COMBINED SECOND-ORDER PARTS OF THE SENTENCE - Bozorboyeva Shaxrizoda Ilhomjon's daughter; Kochkarov son of Javlon Suyundik (Galaxy International Interdisciplinary Research Journal, 2024)
In this article, the function and place of the conjunctive clauses in the sentence is explained with examples. It is also mentioned about the types according to the function performed in the sentence.